PENGARUH MODEL PEMBELAJARAN ROLE PLAYING BERBANTUAN VIDEO INTERAKTIF TERHADAP INTERAKSI SOSIAL DAN PEMAHAMAN KONSEP SISWA SDN PAGERSARI 02 - Sigit Prasetyo; Yuni Purwanti, Kartika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low understanding of Social Studies (IPS) concepts and social interaction among students at SDN Pagersari 02. This study aims to examine the effect of the Role Playing learning model assisted by interactive videos on students' social interaction and conceptual understanding. The research method used is quantitative with a True Experimental design (Pretest-Posttest Control Group Design). The research sample consists of third-grade students selected through simple random sampling techniques. Data collection techniques include essay tests, social interaction questionnaires, observations, and documentation. The results showed a significant increase in students' conceptual understanding, with an increase in the average score and the classical completeness level. Furthermore, the use of interactive video as a visual trigger proved effective in maintaining student attention and improving the quality of social interaction through concrete role simulations. Statistical data indicates that the combination of this model and media has a major influence on improving student learning outcomes. The conclusion of this study is that the use of the Role Playing model assisted by interactive video is effective in creating Social Studies learning that is more meaningful, communicative, and applicable for elementary school students.